Flame-retardant sponge material as well as preparation method and application thereof

Through the coordinated design of the modified oxidized feather-like carbon nanotubes with phosphorus-based flame retardant in flame retardant sponge materials and the phosphorus-containing glycol-containing modified silica aerogel, the problem of difficult to balance the mechanical properties and flame retardant properties of the material is solved, and the flame retardant performance, mechanical properties and thermal stability of the material are significantly improved.

CN119798962AActive Publication Date: 2025-04-11NANTONG FENGSHENG TEXTILE CO LTD

Patent Information

Application Number
CN202510313172.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The existing flame retardant sponge materials are difficult to take into account both the mechanical properties and the flame retardant properties. The dispersion and interface compatibility of the flame retardant are insufficient, resulting in poor overall performance of the material.

Method used

The collaborative design of modified oxidized feathered carbon nanotubes with phosphorus-based flame retardant and phosphorus-containing glycol-containing silica aerogel is improved by introducing phosphorus-based structures on the surface of carbon nanotubes and phosphorus-containing glycol-containing silica aerogels.

Benefits of technology

The flame retardant performance, mechanical properties and thermal stability of flame retardant sponge materials have been significantly improved, and the problems of poor dispersion of flame retardant, weak interface bonding and low flame retardant efficiency have been solved, achieving multiple performance optimization of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798962A_ABST
    Figure CN119798962A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sponge materials, and provides a flame-retardant sponge material as well as a preparation method and application thereof. The flame-retardant flame-retardant coating is prepared from the following components: phosphorus-based flame retardant modified oxidized feather-shaped carbon nanotubes, phosphorus-containing diol modified silicon dioxide aerogel, polyurethane, aluminum hydroxide, ammonium tripolyphosphate, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxidized soybean oil, talcum powder, an antioxidant, a light stabilizer, pigment and antimony trioxide. The composite material is prepared from expanded graphite, a silicone oil surfactant, an isothiazolinone antibacterial agent and a phosphorus-based flame retardant modified oxidized feather-shaped carbon nanotube through wet oxidation and dimethyl methylphosphonate modification, and phosphorus-containing diol is prepared from diethyl phosphite, diethanol amine and paraformaldehyde through condensation. The sponge disclosed by the invention has excellent mechanical and flame-retardant properties, and is widely applied to the fields of buildings, home furnishing and transportation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sponge materials, and in particular to a flame retardant sponge material and a preparation method and application thereof. Background Art

[0002] Flame-retardant sponge materials have a wide range of applications in modern industrial and consumer fields, especially in furniture manufacturing, building decoration, transportation (such as car interiors, airline seats) and electronic equipment, where both comfort and safety need to be taken into account. Flame-retardant properties have become a key indicator for material selection. Due to the flammable nature of their polymer structure, traditional sponge materials may burn quickly and release a large amount of toxic smoke when a fire occurs, seriously threatening personal and property safety. Therefore, the development of sponge materials with excellent flame-retardant properties has become a focus of industry attention. In practical applications, flame-retardant sponge materials not only need to have good flame-retardant properties, such as reducing the burning rate, reducing smoke release and delaying the spread of fire, but also need to show excellent elasticity, compression resistance and durability in terms of mechanical properties to meet the requirements of long-term use. In addition, such materials must also maintain stability in complex environments, be able to adapt to a variety of temperature and humidity conditions and mechanical stress, and be environmentally friendly and low in toxicity to meet the requirements of modern green development. Meeting these performance requirements is of great significance for enhancing the application value of flame-retardant sponge materials, improving the safety of related products and promoting technological progress in the industry. It can not only significantly extend the service life of the materials, but also broaden their application scope in the high-end market, thereby promoting innovation and development in the field of flame-retardant materials.

[0003] At present, although the research and development of flame-retardant sponge materials has made certain progress, there is still a problem that it is difficult to balance mechanical properties and flame retardant properties. For example, the Chinese patent with publication number CN105860392A discloses a method for preparing a polyvinyl alcohol-based sponge material. Although the flame retardant grade of the material is significantly improved, the compatibility of the inorganic flame retardant with the sponge matrix is ​​poor, resulting in a significant decrease in the mechanical properties of the material, which is manifested as deficiencies in compression resistance and resilience. In addition, the Chinese patent with publication number CN108034035A discloses a synergistic flame retardant sponge. Although the modification effectively reduces the burning rate of the material, due to the presence of phosphate and halogen mixed flame retardants, it may not only release toxic fumes, but also pose a potential threat to the environment. The main reason for these deficiencies is that the dispersibility, interface compatibility and damage to the overall structural properties of the material of the flame retardant additives in the prior art are difficult to optimize at the same time, resulting in a significant contradiction between the mechanical properties, environmental protection and flame retardant properties of the material. Therefore, there is an urgent need to develop a new flame-retardant sponge material that can balance mechanical properties and flame retardant properties. By optimizing the design and distribution of flame retardants, the overall performance of the material can be improved, while meeting the multiple requirements of safety, environmental protection and service life, thereby providing a better solution for the field of flame retardant materials. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide a flame retardant sponge material and a preparation method and application thereof, so as to solve the problem that the current sponge is insufficient in mechanical properties and flame retardant properties.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A flame retardant sponge material, comprising the following components, by weight: 3.0-6.5 parts of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes, 4.0-6.5 parts of phosphorus-containing diol modified silica aerogel; 90-110 parts of polyurethane, 20-30 parts of aluminum hydroxide, 1.0-3.0 parts of toluene diisocyanate, 1.0-1.5 parts of deionized water, 0.5-1.5 parts of cyclopentane, and triethanolamine. 0.5~1.5 parts, dibutyltin dilaurate 0.2~0.5 parts, epoxidized soybean oil 5~10 parts, talc 5~10 parts, antioxidant 0.5~1.5 parts, light stabilizer 0.5~1.5 parts, pigment 0.1~0.5 parts, antimony trioxide 3.0~5.0 parts, expanded graphite 5~8 parts, silicone oil surfactant 0.1~0.5 parts, isothiazolinone antibacterial agent 0.1~0.3 parts.

[0006] The phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes are obtained by modifying oxidized feather-like carbon nanotubes with dimethyl methylphosphonate; The oxidized feather-shaped carbon nanotubes are obtained by wet oxidation of carbon nanotubes; The phosphorus-containing diol-modified silica aerogel is obtained by chemically modifying silica aerogel with phosphorus-containing diol in a sol-gel method; The phosphorus-containing diol is prepared by condensation reaction of diethyl phosphite, diethanolamine and paraformaldehyde.

[0007] Furthermore, the preparation method of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes is as follows: in parts by weight, 40 to 60 parts of oxidized feather-like carbon nanotubes, 100 to 140 parts of dimethyl methylphosphonate and 3.0 to 6.0 parts of monobutyl tin oxide are added to a three-well culture bottle, stirred at 160 to 170° C. for 24 to 36 hours, and after the stirring is completed, the temperature is raised to 180 to 185° C. and continued to stir for 30 to 45 minutes to evaporate the unreacted dimethyl methylphosphonate, and after the evaporation is completed, the phosphorus-based flame retardant modified feather-like carbon nanotubes are obtained after cooling to room temperature.

[0008] Further, the preparation method of the oxidized feather-like carbon nanotubes is as follows: by weight, 10 to 20 parts of carbon nanotubes, 4.0 to 8.0 parts of sodium nitrate and 200 parts of 98 wt.% sulfuric acid are mixed in an ice bath, and then stirred at a stirring speed of 200 to 300 rpm for 20 to 30 minutes, while stirring, 25 to 30 parts of potassium permanganate are slowly added to the mixture, and after the stirring is completed, the mixture is stirred in a water bath at 30 to 40° C. for 90 to 120 minutes, and after the stirring is completed, the mixture is slowly added 1000-1200 parts of deionized water are added, and then stirring is continued at 60-80°C for 25-35 minutes to obtain a suspension, and then 30wt.% hydrogen peroxide is slowly added dropwise into the suspension. During the addition process, stirring is continued at a stirring speed of 200-300rpm until the suspension turns bright yellow. The precipitate is then collected by centrifugation, and the precipitate is washed three times with a 10wt.% hydrochloric acid solution. Finally, the washed precipitate is dried in a vacuum drying oven at room temperature for 20-24 hours to obtain oxidized feather-like carbon nanotubes.

[0009] The present invention adopts the design of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes mainly for enhancing the flame retardant performance and structural stability of flame retardant sponge materials. By introducing phosphorus-based flame retardant on the surface of oxidized feather-like carbon nanotubes, carbon nanotubes are given excellent flame retardant performance, and their compatibility with polyurethane matrix is ​​enhanced, further improving the overall flame retardant effect and mechanical properties of the material. In the preparation process, the carbon nanotubes are first treated by wet oxidation to form rich hydroxyl and carboxyl functional groups on their surface, which not only increase the chemical activity of the carbon nanotubes, but also provide binding sites for subsequent phosphorus-based modification. Subsequently, by the reaction of dimethyl methylphosphonate with oxidized feather-like carbon nanotubes, phosphorus-based structures are uniformly introduced on their surfaces, and this modification not only improves the flame retardant performance of carbon nanotubes, but also enhances their dispersibility and interface bonding ability with other components. In the flame retardant sponge material, the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes can form good physical and chemical bonding with the polyurethane matrix, thereby effectively inhibiting the spread of flames and thermal decomposition of materials under high temperature conditions. In addition, this design has good synergy with other components. For example, when it works with aluminum hydroxide and ammonium tripolyphosphate, it can form a stable carbonized layer, further improving the flame retardant efficiency of the material. At the same time, it can work with phosphorus-containing diol-modified silica aerogel to form a dense thermal insulation barrier on the surface of the material, thereby effectively blocking the penetration of heat and oxygen and delaying further combustion of the material. This design not only makes full use of the high specific surface area and excellent mechanical properties of carbon nanotubes, but also significantly improves its flame retardant properties through phosphorus-based modification, ultimately achieving the synergistic optimization of flame retardancy, mechanical properties and material stability.

[0010] In the present invention, the oxidized feather-like carbon nanotubes combine the characteristics of carbon nanotubes and graphene. The feather shaft part is similar to carbon nanotubes, providing excellent mechanical strength and high specific surface area, while the feather part is similar to graphene, with excellent two-dimensional sheet effect and large surface active area. In the flame-retardant sponge material of the present invention, the oxidized feather-like carbon nanotubes are treated by wet oxidation, and a large number of oxygen-containing functional groups (such as hydroxyl and carboxyl) are introduced on the surface of the feather shaft and feather, which significantly improves its dispersibility in the polyurethane matrix and enhances the interface bonding ability with other flame-retardant components and the matrix. The carbon nanotube structure of the feather shaft part plays a mechanical reinforcement role in the material, improving the strength and toughness of the sponge; the graphene structure of the feather part provides excellent flame retardant properties, forming a physical barrier through two-dimensional sheets, effectively blocking the diffusion of heat and oxygen. In addition, the synergistic effect of the oxidized feather-like carbon nanotubes and phosphorus-based flame retardants further enhances the flame retardant effect of the material, can promote the formation of a carbonized layer at high temperature, and inhibit thermal decomposition and flame propagation during combustion. Through this design, the present invention achieves a high degree of coordination among flame retardancy, mechanical properties and material stability, making the sponge material have a wider range of application value in the fields of construction, home furnishing and transportation.

[0011] Further, the preparation method of the phosphorus-containing diol modified silica aerogel is as follows: by weight, 18 to 25 parts of tetraethyl orthosilicate, 45 to 55 parts of anhydrous ethanol and 10 parts of deionized water are mixed and magnetically stirred for 20 to 30 minutes, and then 35 to 42 parts of phosphorus-containing diol are added and stirred for 30 to 45 minutes to obtain a solution A for standby use; 10 to 20 parts of ammonium polyphosphate and 150 parts of anhydrous ethanol are mixed and ultrasonicated for 45 to 60 minutes to obtain a solution B, and then the solution B is added to the mixed solution of the solution A, and then the pH of the mixed solution is adjusted with ammonia water. The pH value of the mixed solution is 7.5-8.0, and then the mixed solution after adjusting the pH value is allowed to stand at 45-50°C for 300-360 min to obtain a gel. The gel is then placed in 200-250 parts of a mixed solution of ethyl orthosilicate and anhydrous ethanol in a volume ratio of 1:1 for aging treatment for 36-48 h. After the treatment, the gel is taken out and placed in 200 parts of n-hexane for standing for 30-42 h. Finally, the treated gel is dried at 50-55°C, 70-75°C and 110-120°C for 2 h, respectively, to obtain a phosphorus-containing diol-modified silica aerogel.

[0012] Furthermore, the preparation method of the phosphorus-containing diol is as follows: in parts by weight, 20 to 30 parts of diethyl phosphite, 18 to 22 parts of diethanolamine, 4.0 to 10.0 parts of paraformaldehyde and 200 parts of chloroform are added in sequence into a three-necked flask equipped with a condensation reflux device and a magnetic stirring device, and then stirred at 50 to 60° C. for 10 to 15 hours, during which the phosphorus-containing diol is synthesized and the solvent is removed, and after the stirring is completed, the mixture is cooled to room temperature to obtain the phosphorus-containing diol.

[0013] The present invention adopts the design of phosphorus-containing diol modified silica aerogel mainly for enhancing the flame retardant and heat insulation properties of flame retardant sponge materials. By preparing phosphorus-containing diol and introducing it into the skeleton structure of silica aerogel, the flame retardant effect and thermal stability of the material are significantly improved. In the technical scheme, the phosphorus-containing diol is prepared by the condensation reaction of diethyl phosphite, diethanolamine and paraformaldehyde. Its molecule contains rich phosphorus elements and hydroxyl structures, which can release phosphorus oxides at high temperatures to form a stable protective layer to inhibit thermal decomposition and flame propagation during combustion. The phosphorus-containing diol is further introduced into the silica aerogel, and its microstructure is regulated by the sol-gel method, so that the modified aerogel has both high specific surface area and excellent thermal insulation performance, and has good flame retardant properties. Silica aerogel itself has excellent heat insulation and low density characteristics, and the introduction of phosphorus-containing diol not only enhances its carbonization ability, but also further improves the material's anti-flame spread ability through the volatile flame retardant mechanism of phosphorus elements. In the composite system of sponge materials, phosphorus-containing diol-modified silica aerogel works synergistically with other flame-retardant components. For example, it works with phosphorus-based flame retardant-modified oxidized feather-like carbon nanotubes to improve the efficiency of carbonization layer formation, and works with ammonium polyphosphate to accelerate the dilution effect of gas during pyrolysis, ultimately achieving a high degree of synergy between flame retardancy and thermal insulation performance. This design optimizes the microstructure and chemical composition, while giving the material excellent flame retardancy, ensuring its lightweight, thermal insulation and environmentally friendly properties, giving it broad application prospects in the fields of construction, home furnishings and transportation.

[0014] Furthermore, the light stabilizer is light stabilizer Tinuvin 770 or light stabilizer Chimassorb 944.

[0015] Furthermore, the pigment is a mixture of one or more of titanium dioxide, red iron oxide or carbon black.

[0016] Furthermore, the silicone oil surfactant is DC-193 water-soluble silicone oil or L-580 silicone oil.

[0017] Furthermore, the isothiazolinone antibacterial agent is methylisothiazolinone.

[0018] The present invention adopts the design of synergistic compounding of flame retardant components, which is mainly used to enhance the flame retardant properties, mechanical properties and comprehensive stability of sponge materials. By combining phosphorus-based flame retardant-modified oxidized feather-like carbon nanotubes with phosphorus-containing diol-modified silica aerogels, and compounding with polyurethane matrix and various additives, multiple performance optimization of the material is achieved. Phosphorus-based flame retardant-modified oxidized feather-like carbon nanotubes provide mechanical reinforcement and flame retardant barrier effects, while phosphorus-containing diol-modified silica aerogels synergistically promote the densification of the carbonized layer at high temperatures, further improving the material's ability to resist flame spread. In addition, aluminum hydroxide and expanded graphite, as inorganic flame retardant components in the material, produce a synergistic effect with the phosphorus-containing flame retardant, which can not only dilute the combustible gas around the flame by releasing non-combustible gas, but also form an insulating carbonized layer at high temperatures, further enhancing the flame retardant effect. Antimony trioxide, as a synergistic flame retardant, works together with phosphorus-based flame retardants, and significantly improves the material's anti-combustion performance through the dual mechanisms of gas phase flame retardancy and condensed phase flame retardancy. Polyurethane is used as a matrix material, and it works together with epoxidized soybean oil, talcum powder and silicone oil surfactant to ensure the mechanical properties, flexibility and stability of the molding process of the sponge material. The addition of antioxidants and light stabilizers enhances the anti-aging properties of the material during long-term use, while isothiazolinone antibacterial agents give the material excellent antibacterial properties, broadening its application field. The components of the present invention achieve a comprehensive improvement in flame retardancy, mechanics, thermal stability and antibacterial properties through synergistic effects. The flame retardant sponge material finally prepared has a wide range of application value and is suitable for various fields such as construction, home furnishing and transportation.

[0019] The present invention also provides a method for preparing a flame retardant sponge material, comprising the following steps: S1. Raw material mixing: polyurethane, aluminum hydroxide, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxy soybean oil, talc, antioxidant, light stabilizer, pigment, antimony trioxide, expanded graphite, silicone oil surfactant, silica aerogel and isothiazolinone antibacterial agent are added into the reactor according to weight proportions, and then stirred at 300-350 rpm for 5-10 min, and then phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel are added and stirred for 10-20 min to obtain a uniformly dispersed mixed solution.

[0020] S2. Foaming treatment: The uniformly dispersed mixed solution obtained in step S1 is heated to 40-60°C for foaming treatment for 30-45 minutes, and then allowed to stand for 30-45 minutes after the foaming treatment to form a preliminarily solidified sponge material.

[0021] S3. Curing treatment: The sponge material initially cured in S2 is dried at 50-70°C, 100-120°C and 150-180°C for 4 hours to complete the curing. After the curing is completed and cooled to room temperature, a flame retardant sponge material is obtained.

[0022] The present invention also provides an application of the flame retardant sponge material in the fields of construction, home furnishing and transportation.

[0023] The present invention adopts a multi-component synergistic compounding design mainly used to enhance the flame retardant properties, mechanical properties and thermal stability of the flame retardant sponge material, while ensuring its light weight, environmental protection and multifunctional characteristics. By optimizing the formula and preparation process, the synergistic effect of each component in the material is fully exerted, and the overall balance and improvement of the performance are achieved. In the preparation method, first, each raw material is added to the reactor in proportion and stirred and mixed, wherein polyurethane is used as a matrix material, which has excellent flexibility and processability, and provides basic mechanical support and molding ability for the flame retardant material; in the preparation process, the foaming step forms a uniform pore structure of the material by heating and stirring, which not only reduces the density but also enhances the thermal insulation; the multi-stage curing treatment further optimizes the microstructure and mechanical properties of the material, so that it has both excellent flame retardant effect and dimensional stability. The flame retardant sponge material prepared by the present invention has a wide range of application value in the fields of construction, home furnishing and transportation, and can meet the multiple needs of flame retardancy, thermal insulation, mechanical properties and environmental protection requirements, and provides a high-performance flame retardant material solution for these fields.

[0024] (3) Beneficial technical effects 1. The present invention significantly improves the flame retardant properties, mechanical properties and thermal stability of flame retardant sponge materials through the synergistic effect of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel. Compared with the existing technology, it solves the pain points of poor dispersibility of flame retardants, weak interface bonding and low flame retardant efficiency. At high temperatures, each component inhibits flame propagation and delays thermal decomposition by forming a dense heat-insulating carbonized layer and a barrier to block oxygen. At the same time, the optimized component ratio and process ensure the synergy of mechanical enhancement and flame retardant efficiency of the material. This invention provides a new idea for the development of environmentally friendly high-performance flame retardant materials and has broad application prospects in the fields of construction, home furnishing and transportation.

[0025] 2. The present invention significantly improves the flame retardant properties, mechanical properties and material stability of the flame retardant sponge through the synergistic effect of oxidized feather-like carbon nanotubes and phosphorus-based flame retardants. Compared with the prior art, it solves the problems of poor dispersibility of flame retardants, weak interface bonding and low flame retardant efficiency. Oxidized feather-like carbon nanotubes combine the mechanical enhancement effect of carbon nanotubes with the two-dimensional barrier effect of graphene to form a dense carbonized layer at high temperature, effectively blocking the diffusion of heat and oxygen; at the same time, its surface functional groups are tightly combined with the matrix and other components to ensure performance synergy. The present invention has broad application value in the fields of construction, home furnishing and transportation, and provides a new direction for the development of high-performance flame retardant materials.

[0026] 3. The present invention significantly improves the flame retardant sponge's anti-combustion performance, mechanical properties and thermal stability through the synergistic effect of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel, combined with inorganic flame retardant components such as aluminum hydroxide, expanded graphite and antimony trioxide. Compared with the prior art, it solves the problems of low flame retardant efficiency, poor durability and insufficient environmental friendliness. Each component synergistically forms a dense heat-insulating carbonized layer at high temperature through optimized ratio, which not only inhibits flame propagation but also delays thermal decomposition. At the same time, the combination of polyurethane matrix and additives ensures the flexibility, anti-aging performance and antibacterial properties of the material, which is suitable for the fields of construction, home and transportation, showing broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope morphology image of the oxidized feather-like carbon nanotubes prepared in Example 1 of the present invention.

[0028] Figure 2 The infrared Fourier spectra of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and the oxidized feather-like carbon nanotubes prepared in Example 1 of the present invention.

[0029] Figure 3 This is the XRD pattern of the ammonium polyphosphate used in Example 1 of the present invention.

[0030] Figure 4 This is the XRD spectrum of the phosphorus-containing diol-modified silica aerogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0032] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0033] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies ; Example 1

[0034] A flame retardant sponge material, comprising the following components in parts by weight: 3.0 parts of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes, 4.0 parts of phosphorus-containing diol modified silica aerogel; 90 parts of polyurethane, 20 parts of aluminum hydroxide, 1.0 parts of toluene diisocyanate, 1.0 parts of deionized water, 0.5 parts of cyclopentane, 0.5 parts of triethanolamine, 0.2 parts of dibutyltin dilaurate, 5 parts of epoxy soybean oil, 5 parts of talc, 0.5 parts of antioxidant, 0.5 parts of light stabilizer Tinuvin 770, 0.1 parts of titanium dioxide, 3.0 parts of antimony trioxide, 5 parts of expanded graphite, 0.1 parts of DC-193 water-soluble silicone oil, and 0.1 parts of methylisothiazolinone; Phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes are obtained by modifying oxidized feather-like carbon nanotubes with dimethyl methylphosphonate; oxidized feather-like carbon nanotubes are obtained by wet oxidation of carbon nanotubes; phosphorus-containing diol modified silica aerogel is obtained by chemically modifying silica aerogel with phosphorus-containing diol in a sol-gel method; phosphorus-containing diol is prepared by condensation reaction of diethyl phosphite, diethanolamine and polyformaldehyde.

[0035] The preparation method of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 40 parts of oxidized feather-like carbon nanotubes, 100 parts of dimethyl methylphosphonate and 3.0 parts of monobutyl tin oxide are added to a three-hole culture bottle, stirred at 160°C for 24 hours, and after the stirring is completed, the temperature is raised to 180°C and stirring is continued for 30 minutes to evaporate the unreacted dimethyl methylphosphonate. After the evaporation is completed, the phosphorus-based flame retardant modified feather-like carbon nanotubes are obtained after cooling to room temperature.

[0036] The preparation method of the oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 10 parts of carbon nanotubes, 4.0 parts of sodium nitrate and 200 parts of 98wt.% sulfuric acid are mixed in an ice bath, and then stirred at a stirring speed of 200rpm for 20min. While stirring, 25 parts of potassium permanganate are slowly added to the mixture, and the mixture is stirred in a water bath at 30°C for 90min. After the stirring is completed, 1000 parts of deionized water are slowly added, and then stirring is continued at 60°C for 25min to obtain a suspension, and then 30wt.% hydrogen peroxide is slowly added dropwise into the suspension, and stirring is continued at a stirring speed of 200rpm during the dropping process until the suspension turns bright yellow, and then the precipitate is collected by centrifugation, and the precipitate is washed 3 times with a 10wt.% hydrochloric acid solution, and finally the washed precipitate is dried in a vacuum drying oven at room temperature for 20h to obtain the oxidized feather-like carbon nanotubes.

[0037] The preparation method of the phosphorus-containing diol modified silica aerogel of the present embodiment is as follows: by weight, 18 parts of tetraethyl orthosilicate, 45 parts of anhydrous ethanol and 10 parts of deionized water are mixed and magnetically stirred for 20 minutes, and then 35 parts of phosphorus-containing diol are added and stirred for 30 minutes to obtain a solution A for standby; 10 parts of ammonium polyphosphate and 150 parts of anhydrous ethanol are mixed and ultrasonicated for 45 minutes to obtain a solution B, and then the solution B is added to the mixed solution of the solution A, and then the pH of the mixed solution is adjusted to 7.5 with ammonia water, and then the mixed solution after the pH is adjusted is allowed to stand at 45° C. for 300 minutes to obtain a gel, and then the gel is placed in a mixed solution of 200 parts of tetraethyl orthosilicate and anhydrous ethanol in a volume ratio of 1:1 for aging treatment for 36 hours, and after the treatment is completed, the gel is taken out and placed in 200 parts of normal hexane for standing for 30 hours, and finally the treated gel is dried at 50° C., 70° C. and 110° C. for 2 hours, respectively, to finally obtain the phosphorus-containing diol modified silica aerogel.

[0038] The preparation method of the phosphorus-containing diol in this embodiment is as follows: 20 parts of diethyl phosphite, 18 parts of diethanolamine, 4.0 parts of paraformaldehyde and 200 parts of chloroform are added in turn into a three-necked flask equipped with a condensation reflux device and a magnetic stirring device, and then stirred at 50° C. for 10 hours. During the stirring process, the phosphorus-containing diol is synthesized and the solvent is removed. After the stirring is completed, the mixture is cooled to room temperature to obtain the phosphorus-containing diol.

[0039] A method for preparing a flame retardant sponge material according to the present embodiment comprises the following steps: S1. Raw material mixing: polyurethane, aluminum hydroxide, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxy soybean oil, talc, antioxidant, light stabilizer Tinuvin770, titanium dioxide, antimony trioxide, expanded graphite, DC-193 water-soluble silicone oil and methylisothiazolinone are added into a reactor according to weight proportions, and then stirred at 300 rpm for 5 min, followed by adding phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel and continuing to stir for 10 min to obtain a uniformly dispersed mixed solution.

[0040] S2. Foaming treatment: The uniformly dispersed mixed solution obtained in step S1 is heated to 40°C for foaming treatment for 60 minutes, and then allowed to stand for 30 minutes after the foaming treatment to form a preliminarily solidified sponge material.

[0041] S3. Curing treatment: The sponge material initially cured in S2 is dried at 50°C, 100°C and 150°C for 4 hours to complete the curing. After the curing is completed and cooled to room temperature, a flame retardant sponge material is obtained.

[0042] Figure 1The scanning electron microscope morphology of the oxidized feather-like carbon nanotubes prepared in Example 1 of the present invention is shown, wherein the darker-colored rachis portion exhibits structural features similar to carbon nanotubes, providing excellent mechanical strength and high specific surface area, while the vane portion exhibits graphene-like morphological features. Figure 2 The infrared Fourier spectra of phosphorus-based flame retardant-modified oxidized feather-like carbon nanotubes and oxidized feather-like carbon nanotubes show that the characteristic absorption peaks at 1204 and 1027 cm⁻¹ correspond to the vibration absorption of P═O and POC groups, respectively, proving that the phosphorus-containing groups were successfully grafted onto the surface of oxidized feather-like carbon nanotubes through dimethyl methylphosphonate. Figure 3 The XRD spectrum of ammonium polyphosphate in Example 1 of the present invention is shown, verifying the validity of its phase. Figure 4 The XRD spectrum of phosphorus-containing diol-modified silica aerogel also proves the effectiveness of its physical phase, indicating that the material prepared by the present invention meets the design requirements in terms of structure and composition. Example 2

[0043] A flame retardant sponge material comprises the following components in parts by weight: 4.1 parts of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes, 4.8 parts of phosphorus-containing diol modified silica aerogel; 96 parts of polyurethane, 23 parts of aluminum hydroxide, 1.6 parts of toluene diisocyanate, 1.2 parts of deionized water, 0.8 parts of cyclopentane, 0.8 parts of triethanolamine, 0.3 parts of dibutyltin dilaurate, 6.5 parts of epoxy soybean oil, 6.5 parts of talc, 0.8 parts of antioxidant, 0.8 parts of light stabilizer Chimassorb944, 0.2 parts of carbon black, 3.6 parts of antimony trioxide, 5.9 parts of expanded graphite, 0.2 parts of L-580 silicone oil and 0.2 parts of methylisothiazolinone.

[0044] Phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes are obtained by modifying oxidized feather-like carbon nanotubes with dimethyl methylphosphonate; oxidized feather-like carbon nanotubes are obtained by wet oxidation of carbon nanotubes; phosphorus-containing diol modified silica aerogel is obtained by chemically modifying silica aerogel with phosphorus-containing diol in a sol-gel method; phosphorus-containing diol is prepared by condensation reaction of diethyl phosphite, diethanolamine and polyformaldehyde.

[0045] The preparation method of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 46 parts of oxidized feather-like carbon nanotubes, 112 parts of dimethyl methylphosphonate and 3.9 parts of monobutyl tin oxide are added to a three-hole culture bottle, stirred at 163°C for 28 hours, and after the stirring is completed, the temperature is raised to 182°C and stirring is continued for 35 minutes to evaporate the unreacted dimethyl methylphosphonate. After the evaporation is completed, the phosphorus-based flame retardant modified feather-like carbon nanotubes are obtained after cooling to room temperature.

[0046] The preparation method of the oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 13 parts of carbon nanotubes, 5.2 parts of sodium nitrate and 200 parts of 98wt.% sulfuric acid are mixed in an ice bath, and then stirred at a stirring speed of 230rpm for 23min. While stirring, 26.5 parts of potassium permanganate are slowly added to the mixture, and the mixture is stirred in a water bath at 33°C for 99min. After the stirring is completed, 1060 parts of deionized water are slowly added, and then stirring is continued at 66°C for 28min to obtain a suspension, and then 30wt.% hydrogen peroxide is slowly dripped into the suspension, and stirring is continued at a stirring speed of 230rpm during the dripping process until the suspension turns bright yellow, and then the precipitate is collected by centrifugation, and the precipitate is washed 3 times with a 10wt.% hydrochloric acid solution, and finally the washed precipitate is dried in a vacuum drying oven at room temperature for 21h to obtain the oxidized feather-like carbon nanotubes.

[0047] The preparation method of the phosphorus-containing diol modified silica aerogel of the present embodiment is as follows: in parts by weight, 20.1 parts of tetraethyl orthosilicate, 48 parts of anhydrous ethanol and 10 parts of deionized water are mixed and magnetically stirred for 23 minutes, and then 37.1 parts of phosphorus-containing diol are added and stirred for 35 minutes to obtain a solution A for use; 13 parts of ammonium polyphosphate and 150 parts of anhydrous ethanol are mixed and ultrasonicated for 50 minutes to obtain a solution B, and then the solution B is added to the mixed solution of the solution A, and then the pH of the mixed solution is adjusted to 7.7 with ammonia water, and then the mixed solution after the pH is adjusted is allowed to stand at 47° C. for 318 minutes to obtain a gel, and then the gel is placed in a mixed solution of 215 parts of tetraethyl orthosilicate and anhydrous ethanol in a volume ratio of 1:1 for aging treatment for 40 hours, and after the treatment is completed, the gel is taken out and placed in 200 parts of normal hexane for 34 hours, and finally the treated gel is dried at 52° C., 72° C. and 113° C. for 2 hours, respectively, to finally obtain the phosphorus-containing diol modified silica aerogel.

[0048] The preparation method of the phosphorus-containing diol in this embodiment is as follows: 23 parts of diethyl phosphite, 19.2 parts of diethanolamine, 5.8 parts of paraformaldehyde and 200 parts of chloroform are added in turn into a three-necked flask equipped with a condensation reflux device and a magnetic stirring device, and then stirred at 53° C. for 12 hours. During the stirring process, the phosphorus-containing diol is synthesized and the solvent is removed. After the stirring is completed, the mixture is cooled to room temperature to obtain the phosphorus-containing diol.

[0049] A method for preparing a flame retardant sponge material according to the present embodiment comprises the following steps: S1. Raw material mixing: polyurethane, aluminum hydroxide, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxy soybean oil, talc, antioxidant, light stabilizer Chimassorb944, carbon black, antimony trioxide, expanded graphite, L-580 silicone oil and methylisothiazolinone are added into the reactor according to weight proportions, and then stirred at 315 rpm for 7 minutes, and then phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel are added and stirred for 13 minutes to obtain a uniformly dispersed mixed solution.

[0050] S2. Foaming treatment: The uniformly dispersed mixed solution obtained in step S1 is heated to 46°C for foaming treatment for 55 minutes, and then allowed to stand for 35 minutes after the foaming treatment to form a preliminarily solidified sponge material.

[0051] S3. Curing treatment: The sponge material preliminarily cured in S2 is dried at 56°C, 106°C and 159°C for 4 hours to complete the curing. After the curing is completed and cooled to room temperature, a flame retardant sponge material is obtained. Example 3

[0052] A flame retardant sponge material comprises the following components in parts by weight: 5 parts of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes, 5.5 parts of phosphorus-containing diol modified silica aerogel; 102 parts of polyurethane, 26 parts of aluminum hydroxide, 2.2 parts of toluene diisocyanate, 1.3 parts of water, 1.1 parts of cyclopentane, 1.1 parts of triethanolamine, 0.4 parts of dibutyltin dilaurate, 8 parts of epoxy soybean oil, 8 parts of talc, 1.1 parts of antioxidant, 1.1 parts of light stabilizer Tinuvin 770, 0.3 parts of red iron oxide, 4.2 parts of antimony trioxide, 6.8 parts of expanded graphite, 0.3 parts of L-580 silicone oil and 0.2 parts of methylisothiazolinone.

[0053] Phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes are obtained by modifying oxidized feather-like carbon nanotubes with dimethyl methylphosphonate; oxidized feather-like carbon nanotubes are obtained by wet oxidation of carbon nanotubes; phosphorus-containing diol modified silica aerogel is obtained by chemically modifying silica aerogel with phosphorus-containing diol in a sol-gel method; phosphorus-containing diol is prepared by condensation reaction of diethyl phosphite, diethanolamine and polyformaldehyde.

[0054] The preparation method of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 52 parts of oxidized feather-like carbon nanotubes, 124 parts of dimethyl methylphosphonate and 4.8 parts of monobutyl tin oxide are added to a three-hole culture bottle, stirred at 166°C for 31 hours, and after the stirring is completed, the temperature is raised to 183°C and stirring is continued for 39 minutes to evaporate the unreacted dimethyl methylphosphonate. After the evaporation is completed, the phosphorus-based flame retardant modified feather-like carbon nanotubes are obtained after cooling to room temperature.

[0055] The preparation method of the oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 16 parts of carbon nanotubes, 6.4 parts of sodium nitrate and 200 parts of 98wt.% sulfuric acid are mixed in an ice bath, and then stirred at a stirring speed of 260rpm for 26min. While stirring, 28 parts of potassium permanganate are slowly added to the mixture, and after stirring, the mixture is stirred in a water bath at 36°C for 108min. After stirring, 1120 parts of deionized water are slowly added, and then stirring is continued at 72°C for 31min to obtain a suspension, and then 30wt.% hydrogen peroxide is slowly dripped into the suspension, and stirring is continued at a stirring speed of 260rpm during the dripping process until the suspension turns bright yellow, and then the precipitate is collected by centrifugation, and the precipitate is washed 3 times with a 10wt.% hydrochloric acid solution, and finally the washed precipitate is dried in a vacuum drying oven at room temperature for 22.4h to obtain the oxidized feather-like carbon nanotubes.

[0056] The preparation method of phosphorus-containing diol modified silica aerogel in this embodiment is as follows: by weight, 22.2 parts of tetraethyl orthosilicate, 51 parts of anhydrous ethanol and 10 parts of deionized water are mixed and magnetically stirred for 26 minutes, and then 39.2 parts of phosphorus-containing diol are added and stirred for 39 minutes to obtain solution A for use; 16 parts of ammonium polyphosphate and 150 parts of anhydrous ethanol are mixed and ultrasonicated for 54 minutes to obtain solution B, and then solution B is added to solution A to mix the mixed solution, and then the mixed solution is adjusted with ammonia water. The pH value of the solution is 7.8, and the mixed solution after adjusting the pH value is allowed to stand at 48°C for 336 minutes to obtain a gel. The gel is then placed in a mixed solution of 230 parts of tetraethyl orthosilicate and anhydrous ethanol in a volume ratio of 1:1 and aged for 43.2 hours. After the treatment, the gel is taken out and placed in 200 parts of n-hexane and allowed to stand for 37.2 hours. Finally, the treated gel is dried at 53°C, 73°C and 116°C for 2 hours, respectively, to obtain phosphorus-containing diol-modified silica aerogel.

[0057] The preparation method of the phosphorus-containing diol in this embodiment is as follows: 26 parts of diethyl phosphite, 20.4 parts of diethanolamine, 7.6 parts of paraformaldehyde and 200 parts of chloroform are added in sequence to a three-necked flask equipped with a condensation reflux device and a magnetic stirring device, and then stirred at 56° C. for 13 hours. During the stirring process, the phosphorus-containing diol is synthesized and the solvent is removed. After the stirring is completed, the mixture is cooled to room temperature to obtain the phosphorus-containing diol.

[0058] A method for preparing a flame retardant sponge material according to the present embodiment comprises the following steps: S1. Raw material mixing: polyurethane, aluminum hydroxide, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxy soybean oil, talc, antioxidant, light stabilizer Tinuvin770, red iron oxide, antimony trioxide, expanded graphite, L-580 silicone oil and methylisothiazolinone are added into a reactor according to weight proportions, and then stirred at 330 rpm for 8 min, followed by adding phosphorus-based flame retardant-modified oxidized feather-like carbon nanotubes and phosphorus-containing diol-modified silica aerogel and continuing to stir for 16 min to obtain a uniformly dispersed mixed solution.

[0059] S2. Foaming treatment: The uniformly dispersed mixed solution obtained in step S1 is heated to 52°C for foaming treatment for 45 minutes, and then allowed to stand for 39 minutes after the foaming treatment to form a preliminarily solidified sponge material.

[0060] S3. Curing treatment: The sponge material preliminarily cured in S2 is dried at 62°C, 112°C and 168°C for 4 hours to complete the curing. After the curing is completed and cooled to room temperature, a flame retardant sponge material is obtained. Example 4

[0061] A flame retardant sponge material comprises the following components in parts by weight: 6.5 parts of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes, 6.5 parts of phosphorus-containing diol modified silica aerogel; 110 parts of polyurethane, 30 parts of aluminum hydroxide, 3.0 parts of toluene diisocyanate, 1.5 parts of deionized water, 1.5 parts of cyclopentane, 1.5 parts of triethanolamine, 0.5 parts of dibutyltin dilaurate, 10 parts of epoxy soybean oil, 10 parts of talc, 1.5 parts of antioxidant, 1.5 parts of light stabilizer Tinuvin770, 0.5 parts of pigment, 5.0 parts of antimony trioxide, 8 parts of expanded graphite, 0.5 parts of L-580 silicone oil and 0.3 parts of methylisothiazolinone; the pigment is a mixture of titanium dioxide, red iron oxide and carbon black in a ratio of 1:1:1.

[0062] Phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes are obtained by modifying oxidized feather-like carbon nanotubes with dimethyl methylphosphonate; oxidized feather-like carbon nanotubes are obtained by wet oxidation of carbon nanotubes; phosphorus-containing diol modified silica aerogel is obtained by chemically modifying silica aerogel with phosphorus-containing diol in a sol-gel method; phosphorus-containing diol is prepared by condensation reaction of diethyl phosphite, diethanolamine and polyformaldehyde.

[0063] The preparation method of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes in this embodiment is as follows: in parts by weight, 60 parts of oxidized feather-like carbon nanotubes, 140 parts of dimethyl methylphosphonate and 6.0 parts of monobutyl tin oxide are added to a three-hole culture bottle, stirred at 170°C for 36 hours, and after the stirring is completed, the temperature is raised to 185°C and stirring is continued for 45 minutes to evaporate the unreacted dimethyl methylphosphonate. After the evaporation is completed, the phosphorus-based flame retardant modified feather-like carbon nanotubes are obtained after cooling to room temperature.

[0064] The preparation method of the oxidized feather-like carbon nanotubes of this embodiment is as follows: in parts by weight, 20 parts of carbon nanotubes, 8.0 parts of sodium nitrate and 200 parts of 98wt.% sulfuric acid are mixed in an ice bath, and then stirred at a stirring speed of 300rpm for 30min. While stirring, 30 parts of potassium permanganate are slowly added to the mixture, and the mixture is stirred in a water bath at 40°C for 120min. After the stirring is completed, 1200 parts of deionized water are slowly added, and then stirring is continued at 80°C for 35min to obtain a suspension, and then 30wt.% hydrogen peroxide is slowly added dropwise into the suspension, and stirring is continued at a stirring speed of 300rpm during the dropping process until the suspension turns bright yellow, and then the precipitate is collected by centrifugation, and the precipitate is washed 3 times with a 10wt.% hydrochloric acid solution, and finally the washed precipitate is dried in a vacuum drying oven at room temperature for 24h to obtain the oxidized feather-like carbon nanotubes.

[0065] The preparation method of the phosphorus-containing diol modified silica aerogel of the present embodiment is as follows: in parts by weight, 25 parts of tetraethyl orthosilicate, 55 parts of anhydrous ethanol and 10 parts of deionized water are mixed and magnetically stirred for 30 minutes, and then 42 parts of phosphorus-containing diol are added and stirred for 45 minutes to obtain a solution A for use; 20 parts of ammonium polyphosphate and 150 parts of anhydrous ethanol are mixed and ultrasonicated for 60 minutes to obtain a solution B, and then the solution B is added to the mixed solution of the solution A, and then the pH of the mixed solution is adjusted to 8.0 with ammonia water, and then the mixed solution after the pH is adjusted is allowed to stand at 50° C. for 360 minutes to obtain a gel, and then the gel is placed in a mixed solution of 250 parts of tetraethyl orthosilicate and anhydrous ethanol in a volume ratio of 1:1 for aging treatment for 48 hours, and after the treatment is completed, the gel is taken out and placed in 200 parts of normal hexane for 42 hours, and finally the treated gel is dried at 55° C., 75° C. and 120° C. for 2 hours, respectively, to finally obtain the phosphorus-containing diol modified silica aerogel.

[0066] The preparation method of the phosphorus-containing diol in this embodiment is as follows: 30 parts of diethyl phosphite, 22 parts of diethanolamine, 10.0 parts of paraformaldehyde and 200 parts of chloroform are added in sequence to a three-necked flask equipped with a condensation reflux device and a magnetic stirring device, and then stirred at 60° C. for 15 hours. During the stirring process, the phosphorus-containing diol is synthesized and the solvent is removed. After the stirring is completed, the mixture is cooled to room temperature to obtain the phosphorus-containing diol.

[0067] A method for preparing a flame retardant sponge material according to the present embodiment comprises the following steps: S1. Raw material mixing: polyurethane, aluminum hydroxide, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxy soybean oil, talc, antioxidant, light stabilizer Tinuvin 770, pigment, antimony trioxide, expanded graphite, L-580 silicone oil and methylisothiazolinone are added into a reactor according to weight proportions, and then stirred at 350 rpm for 10 min, followed by adding phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel and continuing to stir for 20 min to obtain a uniformly dispersed mixed solution.

[0068] S2. Foaming treatment: The uniformly dispersed mixed solution obtained in step S1 is heated to 60°C for foaming treatment for 40 minutes, and then allowed to stand for 45 minutes after the foaming treatment to form a preliminarily solidified sponge material.

[0069] S3. Curing treatment: The sponge material preliminarily cured in S2 is dried at 70°C, 120°C and 180°C for 4 hours to complete the curing. After the curing is completed and cooled to room temperature, a flame retardant sponge material is obtained.

[0070] Comparative Example 1 The method is substantially the same as Example 1, except that the oxidized feather-like carbon nanotubes are not modified with dimethyl methylphosphonate.

[0071] Comparative Example 2 The method is basically the same as Example 1, except that the oxidized feather-like carbon nanotubes are not subjected to wet oxidation treatment, but original carbon nanotubes are used.

[0072] Comparative Example 3 The method is basically the same as Example 1, except that no phosphorus-containing diol is added in the preparation of the phosphorus-containing diol-modified silica aerogel.

[0073] Comparative Example 4 The method is basically the same as Example 1, except that the phosphorus-based flame retardant-modified oxidized feather-like carbon nanotubes are not added in the preparation of the sponge.

[0074] Comparative Example 5 The method is basically the same as Example 1, except that the phosphorus-containing diol-modified silica aerogel is not added in the preparation of the sponge.

[0075] Performance Test: The test methods for sponge materials include the limiting oxygen index method and the vertical combustion method, which are used to characterize their flame retardant properties. The experimental operation of the limiting oxygen index method is carried out in accordance with the national standard "GB / T 5454-1997". In the experiment, 10 specimens with a size of 15 cm × 6 cm were prepared, and the specimens were placed in a gas mixed with oxygen and nitrogen in a certain proportion. The combustion of the specimens was observed, 10 valid data were recorded, and the arithmetic mean was calculated as the limiting oxygen index of the material. The operating steps and evaluation standards of the vertical combustion method are carried out in accordance with the national standard "GB / T 5455-2014". In the experiment, a specimen with a size of 30 cm × 8 cm was prepared, and the specimen was fixed on a fixture for ignition test. The behavior during the combustion process was observed and recorded, including whether thick smoke and molten droplets were generated, the afterburning time (flame burning time) and smoldering time (no flame burning time) of the specimen after the fire source was removed, and the damaged length (mm) of the specimen after the combustion ended.

[0076] Material mechanical properties test: First, take the sponge sample and soak it in PBS buffer with a pH value of 7.4. After the sample completely absorbs the solution and reaches equilibrium, use a vernier caliper to measure the dimensions of the sample and record the data. Then, a compression test was carried out using a universal material testing system. During the experiment, the compression speed was controlled to be maintained at 5 mm / min. In order to protect the equipment, the maximum compression deformation was controlled within 95% during the experiment to obtain the maximum bearing pressure value. According to the measured stress-strain curve, the material toughness value was calculated by the integration method, and the compression modulus was obtained by dividing the stress by the strain. Each formula sample was tested 5 times in parallel, and the data obtained were expressed as mean ± standard deviation (n=5).

[0077] The properties of the sponge materials of Examples 1 to 4 and Comparative Examples 1 to 5 are summarized in Table 2.

[0078] Table 2 Performance of sponge materials of Examples 1 to 4 and Comparative Examples 1 to 5

[0079] In Comparative Example 1, the phosphorus-containing groups were not effectively grafted without modification with dimethyl methylphosphonate, thereby affecting the flame retardant properties (such as reduced limiting oxygen index, afterflaming time and smoldering time). However, due to the reinforcing effect of the oxidized feather-like carbon nanotubes, the mechanical properties (such as compressive strength and toughness) were only slightly lower than those in Example 1. In Comparative Example 2, the original carbon nanotubes that were not treated with wet oxidation were used. Due to the poor interface bonding, not only the flame retardant properties were affected, but also the mechanical properties were reduced, and further reduced than those in Comparative Example 1. However, the original carbon nanotubes still had a certain reinforcing effect, so the compressive strength and toughness remained at a low level. Comparative Example 3 In the comparative example 4, the phosphorus-containing diol was not added, which affected the distribution uniformity and effect of the flame retardant, and the flame retardant performance decreased, but due to the presence of the silica matrix, the mechanical properties were still close to those of the embodiment; in the comparative example 4, the phosphorus-based flame retardant was not added to modify the oxidized feather-like carbon nanotubes, which had the greatest impact on the flame retardant performance, especially the limiting oxygen index, afterflaming time and smoldering time were significantly deteriorated, and the mechanical properties were also greatly affected, with the compressive strength and toughness reduced to the minimum; in the comparative example 5, the phosphorus-containing diol was not added to modify the silica aerogel, which resulted in the loss of the flame retardant effect of the aerogel, and the flame retardant performance decreased significantly, but the basic structure was not completely destroyed, and the mechanical properties were slightly better than those of the comparative example 4.

[0080] In summary, the changes in different components have a significant effect on the flame retardant and mechanical properties of sponge materials. Dimethyl methylphosphonate modification can effectively graft phosphorus-containing groups and significantly improve the flame retardant properties of the material; the oxidized feather-like carbon nanotubes treated by wet oxidation enhance the flame retardant and mechanical properties of the material by improving the interface bonding performance; the addition of phosphorus-containing diols plays a key role in the distribution uniformity and effect of the flame retardant, and at the same time contributes significantly to the flame retardant properties of the material; the introduction of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes significantly improves the comprehensive properties of the material, and the addition of phosphorus-containing diol modified silica aerogel further enhances the flame retardant and mechanical properties of the material. It can be seen that the reasonable design and synergistic effect of each component are crucial to optimizing the overall performance of the material.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A flame retardant sponge material, characterized in that: The invention comprises the following components in parts by weight: 3.0-6.5 parts of phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes, 4.0-6.5 parts of phosphorus-containing diol modified silica aerogel; 90-110 parts of polyurethane, 20-30 parts of aluminum hydroxide, 1.0-3.0 parts of toluene diisocyanate, 1.0-1.5 parts of deionized water, 0.5-1.5 parts of cyclopentane, 0.5-1.5 parts of triethanolamine, 0.2-0.5 parts of dibutyltin dilaurate, 5-10 parts of epoxy soybean oil, 5-10 parts of talc, 0.5-1.5 parts of antioxidant, 0.5-1.5 parts of light stabilizer, 0.1-0.5 parts of pigment, 3.0-5.0 parts of antimony trioxide, 5-8 parts of expanded graphite, 0.1-0.5 parts of silicone oil surfactant, and 0.1-0.3 parts of isothiazolinone antibacterial agent; The phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes are obtained by modifying oxidized feather-like carbon nanotubes with dimethyl methylphosphonate; The oxidized feather-shaped carbon nanotubes are obtained by wet oxidation of carbon nanotubes; The phosphorus-containing diol-modified silica aerogel is obtained by chemically modifying silica aerogel with phosphorus-containing diol in a sol-gel method; The phosphorus-containing diol is prepared by condensation reaction of diethyl phosphite, diethanolamine and paraformaldehyde.

2. A flame retardant sponge material according to claim 1, characterized in that: The preparation method of the phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes is as follows: by weight, 40-60 parts of oxidized feather-like carbon nanotubes, 100-140 parts of dimethyl methylphosphonate and 3.0-6.0 parts of monobutyl tin oxide are added into a three-hole culture bottle, stirred at 160-170° C. for 24-36 hours, heated to 180-185° C. after the stirring is completed, and stirred for 30-45 minutes to evaporate the unreacted dimethyl methylphosphonate, and cooled to room temperature after the evaporation is completed to obtain the phosphorus-based flame retardant modified feather-like carbon nanotubes.

3. A flame retardant sponge material according to claim 1 or 2, characterized in that: The preparation method of the oxidized feather-like carbon nanotubes is as follows: by weight, 10 to 20 parts of carbon nanotubes, 4.0 to 8.0 parts of sodium nitrate and 200 parts of 98 wt.% sulfuric acid are mixed in an ice bath, and then stirred at a stirring speed of 200 to 300 rpm for 20 to 30 minutes, while stirring, 25 to 30 parts of potassium permanganate are slowly added to the mixture, and after the stirring is completed, the mixture is stirred in a water bath at 30 to 40° C. for 90 to 120 minutes, and after the stirring is completed, 10 00~1200 parts of deionized water are added, and then stirring is continued at 60~80°C for 25~35min to obtain a suspension, and then 30wt.% hydrogen peroxide is slowly added dropwise into the suspension. Stirring is continued at a stirring speed of 200~300rpm during the dropping process until the suspension turns bright yellow, and then the precipitate is collected by centrifugation, and the precipitate is washed three times with 10wt.% hydrochloric acid solution. Finally, the washed precipitate is dried in a vacuum drying oven at room temperature for 20~24h to obtain oxidized feather-like carbon nanotubes.

4. A flame retardant sponge material according to claim 1, characterized in that: The preparation method of the phosphorus-containing diol modified silica aerogel is as follows: by weight, 18-25 parts of tetraethyl orthosilicate, 45-55 parts of anhydrous ethanol and 10 parts of deionized water are mixed, and then magnetically stirred for 20-30 minutes, and then 35-42 parts of phosphorus-containing diol are added and stirred for 30-45 minutes to obtain a solution A for standby use; 10-20 parts of ammonium polyphosphate and 150 parts of anhydrous ethanol are mixed and ultrasonicated for 45-60 minutes to obtain a solution B, and then the solution B is added to the solution A to obtain a mixed solution, and then the pH of the mixed solution is adjusted to 7 with ammonia water. .5~8.0, and then the mixed solution after adjusting the pH is allowed to stand at 45~50℃ for 300~360min to obtain a gel, and then the gel is placed in 200~250 parts of a mixed solution of tetraethyl orthosilicate and anhydrous ethanol with a volume ratio of 1:1 for aging treatment for 36~48h. After the treatment, the gel is taken out and placed in 200 parts of n-hexane for standing for 30~42h. Finally, the treated gel is dried at 50~55℃, 70~75℃ and 110~120℃ for 2h respectively to obtain phosphorus-containing diol modified silica aerogel.

5. A flame retardant sponge material as claimed in claim 1 or 4, characterized in that: The preparation method of the phosphorus-containing diol is as follows: by weight, 20 to 30 parts of diethyl phosphite, 18 to 22 parts of diethanolamine, 4.0 to 10.0 parts of paraformaldehyde and 200 parts of chloroform are added in sequence into a three-necked flask equipped with a condensation reflux device and a magnetic stirring device, and then stirred at 50 to 60° C. for 10 to 15 hours, during which the phosphorus-containing diol is synthesized and the solvent is removed, and after the stirring is completed, the mixture is cooled to room temperature to obtain the phosphorus-containing diol.

6. A flame retardant sponge material according to claim 1, characterized in that: The light stabilizer is light stabilizer Tinuvin 770 or light stabilizer Chimassorb 944; The pigment is a mixture of one or more of titanium dioxide, red iron oxide or carbon black.

7. A flame retardant sponge material according to claim 1, characterized in that: The silicone oil surfactant is DC-193 water-soluble silicone oil or L-580 silicone oil; The isothiazolinone antibacterial agent is methylisothiazolinone.

8. The method for preparing a flame retardant sponge material according to claim 1, characterized in that: The following steps are involved: S1. Mixing raw materials: polyurethane, aluminum hydroxide, toluene diisocyanate, deionized water, cyclopentane, triethanolamine, dibutyltin dilaurate, epoxy soybean oil, talc, antioxidant, light stabilizer, pigment, antimony trioxide, expanded graphite, silicone oil surfactant and isothiazolinone antibacterial agent are added to the reactor according to weight parts, and then stirred at 300-350 rpm for 5-10 minutes, and then phosphorus-based flame retardant modified oxidized feather-like carbon nanotubes and phosphorus-containing diol modified silica aerogel are added and stirred for 10-20 minutes to obtain a uniformly dispersed mixed solution; S2. Foaming treatment: The uniformly dispersed mixed solution obtained in step S1 is heated to 40 to 60 ° C for foaming for 30 to 45 minutes, and then allowed to stand for 30 to 45 minutes after the foaming treatment to form a preliminary cured sponge material; S3. Curing treatment: The preliminarily cured sponge material obtained in S2 is dried at 50-70°C, 100-120°C and 150-180°C for 4 hours to complete the curing. After the curing is completed and cooled to room temperature, a flame retardant sponge material is obtained.

9. Application of the flame retardant sponge material as claimed in claim 1 in the fields of construction, home furnishing and transportation.

Citation Information

Patent Citations

  • Preparation method of polyvinyl alcohol-based sponge material

    CN105860392A

  • Synergistic flame-retardant sponge

    CN108034035A

  • A method for preparing diethyl N,N-bis(2-hydroxyethyl)aminomethylphosphonate

    CN102276645A

  • Method for preparing graphene / carbon nanotube composite material

    CN106241782A

  • Method for preparing carbon nanotube / graphene hybrid electrically conductive material through one-step hydrothermal method

    CN107381546A

Cited By

  • Polyurethane-based foaming composite material containing carbon black and preparation method thereof

    CN120682443A